2006
DOI: 10.1103/physrevlett.96.115002
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Magnetohydrodynamic Turbulence

Abstract: We propose a phenomenological theory of strong incompressible magnetohydrodynamic turbulence in the presence of a strong large-scale external magnetic field. We argue that in the inertial range of scales, magnetic-field and velocity-field fluctuations tend to align the directions of their polarizations. However, the perfect alignment cannot be reached; it is precluded by the presence of a constant energy flux over scales. As a consequence, the directions of shear-Alfvén fluid and magnetic-field fluctuations at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

68
622
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(698 citation statements)
references
References 19 publications
68
622
8
Order By: Relevance
“…The rate of occurrence of the linear scaling in the solar wind time series, and the corresponding energy transfer rate, have been related to several solar wind parameters. For example, the energy transfer rate has been shown to anti-correlate with the cross-helicity level Stawarz et al 2010;Marino et al 2011Marino et al , 2012Podesta 2011), confirming that alignment between velocity and magnetic field reduces the turbulent cascade, as expected for Alfvénic turbulence (Dobrowolny et al 1980;Boldyrev 2006). Relationships with heliocentric distance and solar activity have also been pointed out, with controversial results (Marino et al 2011(Marino et al , 2012Coburn et al 2012).…”
Section: Energy Transfer Ratementioning
confidence: 89%
See 1 more Smart Citation
“…The rate of occurrence of the linear scaling in the solar wind time series, and the corresponding energy transfer rate, have been related to several solar wind parameters. For example, the energy transfer rate has been shown to anti-correlate with the cross-helicity level Stawarz et al 2010;Marino et al 2011Marino et al , 2012Podesta 2011), confirming that alignment between velocity and magnetic field reduces the turbulent cascade, as expected for Alfvénic turbulence (Dobrowolny et al 1980;Boldyrev 2006). Relationships with heliocentric distance and solar activity have also been pointed out, with controversial results (Marino et al 2011(Marino et al , 2012Coburn et al 2012).…”
Section: Energy Transfer Ratementioning
confidence: 89%
“…Beyond the anisotropy of the fluctuations with respect to the magnetic field direction, (Boldyrev 2006) also suggested that the turbulence can be anisotropic with respect to the local fluctuation direction -and that this anisotropy will be scale dependent. Remarkably, in the solar wind observations there is some recent evidence for the scale-dependent alignment predicted by this theory at large scales (Podesta et al 2009b) and for the local 3D anisotropy small scales .…”
Section: Magnetic Fluctuationsmentioning
confidence: 99%
“…The transition wavenumber for the γ GS k = γ NL k↑↑ transition is practically the same, k ⊥1 ρ p 0.6. However, the above estimations did not take into account the weakening of the MHD nonlinear interactions by the dynamic alignment between velocity and magnetic perturbations (Boldyrev, 2005) and/or by the nonlocal decorrelation mechanism proposed by Gogoberidze (2007). In general, the interaction rate can be written as a reduced GS rate (RGS)…”
Section: Spectral Kinksmentioning
confidence: 99%
“…This symmetric case where the fluxes of oppositely directed Alfvén waves are equal does not however strictly apply to the solar wind (Goldreich and Sridhar, 1997), where the fluxes are observed to be asymmetric. Recent numerical simulations (Müller and Grappin, 2005), and analysis (Boldyrev, 2006 hereafter SB) obtain a ∼k −3/2 ⊥ spectrum for the case of a strong local background magnetic field. This −3/2 exponent, combined with the anisotropy of the fluctuations, is in contradiction with WI (either isotropic, −3/2 exponent or anisotropic, −2 exponent) and SA (anisotropic, −5/3 exponent) phenomenologies.…”
Section: Scaling Exponents Mhd Turbulence Models and Similarity Analmentioning
confidence: 99%